DESAIN BATIK BERBASIS KEARIFAN LOKAL: INOVASI KREATIF DALAM MEWUJUDKAN KEMANDIRIAN EKONOMI PESANTREN - Nailatur Rohmah; Ah. Shibghatullah Mujaddidi (IAIN BONE, 2025)
Islamic boarding schools play a vital role in fostering economic independence through the development of creative industries rooted in local wisdom. This study focuses on Darussalam Islamic Boarding School, Billapora Timur, Sumenep, which initiated a batik enterprise known as Batik Gungsumi. The innovation utilizes ancient local manuscripts as the source of inspiration for batik motifs, producing cultural and spiritual values alongside economic benefits. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving school leaders, students, and alumni engaged in the batik business. The findings indicate that Batik Gungsumi significantly contributes to pesantren’s economic independence by generating sustainable income, creating job opportunities, and enhancing students’ entrepreneurial skills. Moreover, the creative reinterpretation of manuscript-based motifs strengthens cultural identity and improves competitiveness within the creative industry. Consequently, Batik Gungsumi serves not only as an instrument of pesantren’s economic empowerment but also as a medium for cultural preservation and a learning platform that balances religious education with entrepreneurship in facing modern challenges.